2013
DOI: 10.4236/ns.2013.511146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sleeping patterns on academic performance in medical school students

Abstract: In the past, efforts have been made to determine the influence of sleep quantity and its deprivation, on functioning efficiency of human beings. However, determination of sleeping patterns that could improve intellectual performance has been largely neglected. This study is designed to discover the effects of different sleeping patterns on academic performance among medical students. A descriptive study was carried out in King Edward Medical University in Lahore, Pakistan during a six-month time span from May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
4
Order By: Relevance
“…Sleep is undoubtedly an important aspect of a successful academic and economically prosperous career. Students who well understand the importance of a proper sleeping habit can improve their academic performance where usually it is noted that adults require 8 hours sleep a day [ 8 , 9 ]. In the modern society, sleep disturbances have become quite frequent along with which several risk factors have also been identified like female gender, depression, snoring, nocturnal micturition, use of hypnotic drugs, stressful lifestyle [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is undoubtedly an important aspect of a successful academic and economically prosperous career. Students who well understand the importance of a proper sleeping habit can improve their academic performance where usually it is noted that adults require 8 hours sleep a day [ 8 , 9 ]. In the modern society, sleep disturbances have become quite frequent along with which several risk factors have also been identified like female gender, depression, snoring, nocturnal micturition, use of hypnotic drugs, stressful lifestyle [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mulazim Hussain Bukhari (2013) 7 who found that there is no significance among two variable sleep pattern and academic performance of medical students.Study done by Raphael, Gilbert odille (2014) 8 was contradictory to present study which shows that there was positive correlation between sleep quality and academic performance. Study results AK.…”
Section: Keymentioning
confidence: 99%
“…Hal ini membuat mahasiswa kedokteran memiliki kualitas tidur yang buruk sehingga berdampak pada penurunan atensi dan konsentrasi saat proses belajar, serta disfungsi aktivitas di siang hari seperti adanya rasa kantuk yang berlebihan di siang hari. 15 Berdasarkan latar belakang yang telah diuraikan di atas, dilakukan penelitian untuk mengetahui apakah terdapat hubungan antara kualitas tidur dengan atensi pada mahasiswa/i Fakultas Kedokteran Universitas HKBP Nommensen.…”
Section: Pendahuluanunclassified